Rancang Bangun Alat Timbangan Digital dengan Load Cell Sensor - M. Ridwan Arif Cahyono; Dharmanto; Rian Febrianto (Jurnal Instrumentasi dan Teknologi Informasi (JITI), 2026)
Workers in the rigid foam block weighing area at PT IIA are exposed to ergonomic risks due to repetitive manual tasks and non-ideal working postures. These conditions can lead to musculoskeletal complaints and increase the risk of Musculoskeletal Disorders (MSDs). This study aims to design and develop an ergonomic digital weighing device using a load cell sensor to reduce occupational risks and improve production process efficiency. Postural analysis using the Rapid Entire Body Assessment (REBA) method was conducted to evaluate ergonomic risks prior to equipment design. The weighing tool was designed based on workers' anthropometric dimensions and tested to ensure weight measurement accuracy through calibration and sensor linearity testing. The test results show an average error rate of only 0.024%, which falls within the acceptable tolerance limits of the sensor. Therefore, the digital weighing device is considered ergonomic, accurate, and feasible for use in the production process.